1999
DOI: 10.1093/emboj/18.11.3153
|View full text |Cite
|
Sign up to set email alerts
|

The yeast poly(A)-binding protein Pab1p stimulates invitro poly(A)-dependent and cap-dependent translation by distinct mechanisms

Abstract: Translation initiation in extracts fromSaccharomyces cerevisiae involves the concerted action of the capbinding protein eIF4E and the poly(A) tail-binding protein Pab1p. These two proteins bind to translation initiation factor eIF4G and are needed for the translation of capped or polyadenylated mRNA, respectively. Together, these proteins synergistically activate the translation of a capped and polyadenylated mRNA. We have discovered that excess Pab1p also stimulates the translation of capped mRNA in extracts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
126
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(136 citation statements)
references
References 29 publications
(77 reference statements)
8
126
0
2
Order By: Relevance
“…In addition, the effect of binding of full-length eIF4G on the cap affinity of eIF4E can be further enhanced through binding of the PABP to eIF4G (4,9,12,48). PABP can also modulate cap-dependent translation in the absence of a direct interaction with eIF4G, raising the possibility that PABP forms contacts with other factors at the 5Ј end of mRNA (30). Therefore, signaling pathways may selectively enhance eIF4GII recruitment to the cap structure either by acting directly on the eIF4GII protein or by modulating eIF4E, PABP, or other specific eIF4GII partners or even by acting on some selective PABP partners, which would strengthen eIF4G-cap interaction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the effect of binding of full-length eIF4G on the cap affinity of eIF4E can be further enhanced through binding of the PABP to eIF4G (4,9,12,48). PABP can also modulate cap-dependent translation in the absence of a direct interaction with eIF4G, raising the possibility that PABP forms contacts with other factors at the 5Ј end of mRNA (30). Therefore, signaling pathways may selectively enhance eIF4GII recruitment to the cap structure either by acting directly on the eIF4GII protein or by modulating eIF4E, PABP, or other specific eIF4GII partners or even by acting on some selective PABP partners, which would strengthen eIF4G-cap interaction.…”
Section: Discussionmentioning
confidence: 99%
“…(89) This hypothesis is further supported by targeted mutational studies of conserved amino acids in this region. (91) Structural data is also available for the PABC domain. (92,93) This conserved sequence of 74 amino acids in length consists of five a-helices arranged in the shape of an arrow and binds specifically through a hydrophobic region to an approximately 12 amino acid peptide motif present in a number of confirmed interaction partners.…”
Section: Assembly Of the 80s Ribosomementioning
confidence: 99%
“…One important aspect of translation initiation that might not be accommodated by the closed-loop model is the ability of PABP to stimulate the translation of nonpolyadenylated mRNAs. This regulation was first reported for a yeast system in vitro (37). Sachs and colleagues (37) defined this phenomenon as transactivation, suspecting that it is mediated by PABP that is not directly bound to mRNA.…”
Section: Discussionmentioning
confidence: 85%
“…Supporting the possibility of PABP acting in trans, PABP mutants with reduced RNA binding activity stimulated translation (37). Given that an A stretch is required for the interaction between eIF4G and PABP in yeast (10), it was suggested that a factor(s) other than eIF4G is targeted by PABP within the translation initiation complex (37). However, the PABP binding sites in yeast and mammalian eIF4G markedly differ, and the presence of poly(A) is not necessary for the human eIF4G-PABP interaction.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation